Speech Act in a Courtroom: An Analysis of Chris Watts Trial - Heidi, Juliana; Setyaningsih, Nina (Universitas PGRI Semarang, 2024)
The utterances produced by participants in a trial relates to their role and the trial stage. Therefore, everyone involved in the trial will produce a variety of speech acts. This research aims to describe the types of speech act in Chris Watts trial and to describe the functions of the speech act used in the trial. The analysis is based on Searle's theory of speech act (1979). The researchers used descriptive qualitative method to describe the types of speech act and the functions of the speech acts by analyzing each utterance produced by all of the participants in courtroom. The finding shows that there are 176 utterances of speech acts which consist of 79 representatives, 23 directives, 14 commissives, 51 expressive, and 9 declarations. The researchers also found 26 functions of speech act. The dominant speech act in Chris Watts trial is representative, because all the participants give statements of fact about the case during the trial. Moreover, the most frequently used function of speech act in Chris Watts trial is stating, because, most of the participants' utterance is used to state their belief and thought regarding Chris Watts case. In this research, the specific position of the speaker in the courtroom creates specific function of speech act used. The witnesses utterance is used to condemn the defendant, the judges utterance is used to sentence the defendant, while the prosecutors utterance is used to restate the witnesss statement.